Optimizing novel penetration enhancing hybridized vesicles for augmenting the in-vivo effect of an anti-glaucoma drug - Sarah S. Naguib; Rania M. Hathout; Samar Mansour (Taylor & Francis Group, 2017)
Usually the topical delivery of ocular drugs poses a great challenge. Accordingly, the work in this study comprised the use of different hybrids of generally regarded as safe (GRAS) oils and surfactants in order to develop and optimize novel acetazolamide (AZD) entrapped-vesicular systems aiming at improving its ocular delivery and reaching better therapeutic outcomes in the treatment of glaucoma. The phospholipid/cholesterol bilayer of the vesicles was enriched with hybrids of Tween 80, Labrasol, Transcutol and Labrafac lipophile WL in different masses and proportions according to a mixture design viz. D-optimal mixture design. Three models were generated comprising three responses: particles size, percentage of entrapment efficiency and amount of drug released after 24 hours (Q24h). The results demonstrated the ability of the penetration enhancing hybrids in modulating the three responses compared to the conventional liposomes. Transmission electron microscope was used to characterize the selected formulations. Sterilization of selected formulations was carried out using gamma radiation and the effect of gamma radiations on entrapment, particle size and in vitro release were studied. The selected sterilized formulations were tested in-vivo on the eyes of albino rabbits in order to evaluate the efficiency of the novel delivery systems on the intra-ocular pressure reduction (IOP) compared to drug solution and the conventional liposomes. The novel formulations proved their efficiency in reducing the IOP to lower values compared to the conventional liposomes, which pose new successful platform for ocular delivery of AZD and other anti-glaucoma drug analogs.